A New Conception of War : John Boyd, the U.S. Marines, and Maneuver Warfare - Brown, Ian T. (Book collections on Project MUSE., 2018)
The purpose of this book is to examine John Boyd's early life and military career, outlining how he exhibited his personal drive to be useful and how he applied it from the open skies of aerial combat to the halls of the Pentagon. It also discusses his first glimmerings of a grander idea of conflict, developed from several insights gleaned through decades of military service. From there, it outlines the Marine Corps' tradition of adapting to remain useful and places it in the context of an institutional realization that the post-Vietnam world required another adaptive leap to retain its advertised utility. It continues with a discussion of initial attempts by Marines and interested civilians to find answers to two key questions--what was the Corps' role in the new threat environment, and what organizing principle should it use to fulfill this role--and concludes with the initial discussions about the maneuver warfare concept, which a handful of thinkers believed was the answer to those questions. The book then returns to Boyd and his development of the ideas on conflict that would become the intellectual foundation of maneuver warfare. It illustrates the key events that ultimately led him to create a mental framework for conceptualizing survival and decision making as described in his essay, "Destruction and Creation," and then applying that framework to the realm of warfare in "Patterns of Conflict." After summarizing the central insights from those two works, it explains general misconceptions about each that arose as Boyd's theories gained a wider audience and shows how the ideas from "Patterns of Conflict" became enmeshed with the debate about maneuver warfare.--Provided by publisher.